Polymers in Regenerative Medicine. - Monleon Pradas, Manuel (Wiley, 2015)
Biomedical applications of Polymers from Scaffolds toNanostructures The ability of polymers to span wide ranges of mechanicalproperties and morph into desired shapes makes them useful for avariety of applications, including scaffolds, self-assemblingmaterials, and nanomedicines. With an interdisciplinary list ofsubjects and contributors, this book overviews the biomedicalapplications of polymers and focuses on the aspect of regenerativemedicine. Chapters also cover fundamentals, theories, and tools forscientists to apply polymers in the following ways: Matrix protein interactions with synthe.